Study on the moisture permeability of warp-knitted Jacquard shoe upper material based on CFD - Lujiao Zuo; Qi Zhang; Jiani Tu; Meiting Nie (Scientific Reports)
Abstract Developing warp-knitted Jacquard upper material is a laborious process, and conducting performance testing is intricate. Therefore, it is imperative to establish a predictive method for fabric performance. In this research, samples were extracted from the abrasion-resistant and breathable sections of the shoe upper material. The influence of mesh structure and its distribution on the moisture permeability of the shoe upper material was investigated through practical experiments and numerical simulations. Sample modeling was carried out using SolidWorks software. The effective structure was identified based on the fabric model, and the fluid domain was isolated. Fluent software was employed to perform numerical simulations of moisture permeability within the fluid domain model, with subsequent comparison between experimental data and simulation outcomes. The results revealed a strong correlation between the simulated structure and the measured performance, indicating that mesh structure plays a critical role in enhancing moisture permeability of the upper material. Additionally, by independently modifying yarn fineness and spacer yarn count in an existing model, the impact of these parameters on moisture permeability in shoe upper material was explored. The investigation suggested that for areas requiring wear resistance, flat layers should be positioned as base layers, and spacer layers should follow a 2-1-1-0/1-2-2-3// yarn laying pattern. Furthermore, regions requiring air permeability should incorporate an optimal amount of mesh structure to improve moisture permeability. In terms of wear comfort, mesh structures are recommended as surface layers in air permeability zones.